The control of an uncharted pinning point on the flow of an Antarctic ice shelf - Berger, Sophie; Favier, Lionel; Drews, Reinhard; Derwael, Jean-Jacques; Pattyn, Frank (2016)
Antarctic ice shelves are buttressed by numerous pinning points attaching to the otherwise freely-floating ice from below. Some of these kilometric-scale grounded features are unresolved in Antarctic-wide datasets of ice thickness and bathymetry, hampering ice-flow models to fully capture dynamics at the grounding line and upstream. We investigate the role of a 8.7 km2 pinning point at the front of the Roi Baudouin Ice Shelf, East Antarctica. Using ERS interferometry and ALOS-PALSAR speckle tracking, we derive, on a 125 m grid spacing, surface velocities deviating from 37 on-site GNSS measurements with -5.2± 4.5 m a−1 .We find no evidence for ice-flow changes on decadal time scales and show that ice on the pinning point virtually stagnates, deviating the ice stream and causing enhanced horizontal shearing upstream. Using the BISICLES ice-flow model, we invert for basal friction and ice rigidity with three input scenarios of ice velocity and geometry. We show that inversion results are the most sensitive to the presence/absence of the pinning point in the bathymetry, surface velocities at the pinning point are of secondary importance. Undersampling of pinning points results in erroneous ice-shelf properties in models initialised by control methods. This may impact prognostic modelling for ice-sheet evolution in case of unpinning. SCOPUS: ar.j info:eu-repo/semantics/published